The bumpy road of assessment for learning during pandemic of COVID-19 - Hieronimus Canggung Darong; Erna Mena Niman (Journal of Education and Learning (EduLearn), 2023)
A worldwide discussion about the practice of assessment for learning (AfL) in online classes during the pandemic COVID-19 is scarce. The current research can have a significant impact on teaching and learning practices, and contribute to the development of evidence-based policies and practices that support student success. Thus, the current study aimed at exploring English teachers’ AfL practice in online classes. This study belonged to a basic qualitative approach and recruited four English foreign language or EFL teachers from the secondary school level. Observation and semi-structured interviews using an interview guide were conducted to gain the data. To ensure the trustworthiness of the data, other documents were collected. Subsequently, utilizing the spiral strategy, the gained data were analyzed. The results revealed that the implementation of AfL deviated from the course. Insufficient knowledge, curriculum, internet accessibility, and technological acceptance are pivotal causes of such deviation. Thus, teachers might not diagnose students’ current learning level and decide on a further teaching action. Further studies on other educational levels are demanded to explore the practice of AfL.